Prevalence and clinical outcomes of pleural effusion in COVID‐19 patients: A systematic review and meta‐analysis. Issue 1 (1st September 2021) - Rathore, Sawai Singh; Hussain, Nabeel; Manju, Ade Harrison; Wen, Qingqing; Tousif, Sohaib; Avendaño‐Capriles, Camilo Andrés; Hernandez‐Woodbine, Maria Jose; Rojas, Gianpier Alonzo; Vatsavayi, Priyanka; Tera, Chenna Reddy; Ali, Muhammad Adnan; Singh, Romil; et al.
Abstract: Observational studies indicate that pleural effusion has an association with risk and the clinical prognosis of COVID‐19 disease; however, the available literature on this area is inconsistent. The objective of this systematic review and meta‐analysis is to evaluate the correlation between COVID‐19 disease and pleural effusion. A rigorous literature search was conducted using multiple databases. All eligible observational studies were included from around the globe. The pooled prevalence and associated 95% confidence interval (CI) were calculated using the random effect model. Mantel–Haenszel odds ratios were produced to report overall effect size using random effect models for severity and mortality outcomes. Funnel plots, Egger regression tests, and Begg–Mazumdar's rank correlation test were used to appraise publication bias. Data from 23 studies including 6234 COVID‐19 patients was obtained. The overall prevalence of pleural effusion in COVID‐19 patients was 9.55% (95% CI, I 2 = 92%). Our findings also indicated that the presence of pleural effusions associated with increased risk of severity of disease(OR = 5.08, 95% CI 3.14–8.22, I 2 = 77.4%) and mortality due to illness(OR = 4.53, 95% CI 2.16–9.49, I 2 = 66%) compared with patients without pleural effusion. Sensitivity analyses illustrated a similar effect size while decreasing the heterogeneity. No significant publication bias was evident in the meta‐analysis. The presence of pleural effusion can assist as a prognostic factor to evaluate the risk of worse outcomes in COVID‐19 patients hence, it is recommended that hospitalized COVID‐19 patients with pleural effusion should be managed on an early basis. Highlights: Pleural effusion associated with COVID‐19 is less common in clinical settings. The overall pooled prevalence of pleural effusion in COVID‐19 patients was found to be 9.55%. The presence of pleural effusion in COVID‐19 patients is associated with increased severity of disease and mortality due to illness compared with patients without pleural effusion The presence of pleural effusion can assist as a prognostic factor to evaluate the risk of worse outcomes in COVID‐19 patients